Analysis of Vulnerability Tsunami in Morowali Regency, Central Sulawesi - Adriansyah, Muh. Syukron; Chaerul, Muhammad; Marzuki, Ismail; Erniati, Erniati; Desy, Natsar; Harun, A. Muh. Yusuf (ASTONJADRO, 2026)
Indonesia is one of the countries located within the Pacific Ring of Fire, characterized by high tectonic activity and vulnerability to various natural disasters, including earthquakes and tsunamis. One of the regions in Eastern Indonesia with tsunami hazard potential is Sulawesi Island, particularly Central Sulawesi Province. The tsunami potential in this region is influenced by the presence of active faults, including the Palu-Koro Fault, which is connected to several minor faults, one of which is the Matano Fault located in Morowali Regency. Based on USGS earthquake data from 2019–2024, seismic events in both onshore and offshore areas of Morowali Regency have continuously occurred, with magnitudes ranging from M 2.9 to M 5.1. This study aims to assess tsunami vulnerability levels based on social, physical, economic, and environmental parameters, as well as to identify appropriate mitigation measures to reduce the potential impacts of tsunami hazards in Morowali Regency. The research method employed a Geographic Information System (GIS) approach using scoring and overlay techniques to determine areas with low, medium, and high vulnerability levels. The analysis indicates that Morowali Regency has a high level of tsunami vulnerability across social, physical, economic, and environmental parameters. Based on these findings, appropriate mitigation measures include both structural and non-structural strategies. Structural mitigation involves the development of early warning systems, evacuation routes and signage, tsunami safe zones, as well as the construction of water breaks and coastal greenbelts (mangroves). Non-structural mitigation includes community outreach on tsunami hazards, the formulation of regional regulations on coastal development, establishment of disaster response task forces at the neighborhood or village level, and conducting tsunami disaster mitigation simulation drills.